Graphical models for security : 4th International Workshop, GraMSec 2017, Santa Barbara, CA, USA, August 21, 2017, Revised selected papers /: 4th International Workshop, GraMSec 2017, Santa Barbara, CA, USA, August 21, 2017, Revised selected papers. (2018) - Unknown
No abstract available